EFEKTIVITAS METODE BERCERITA DALAM MENINGKATKAN KEMAMPUAN BERBICARA SISWA KELAS 1 SDN 1 PATAKAHARJA - Heti Sutiartini; Rahmat Hidayat; Sri Sugiarti (Sekolah Tinggi Agama Islam Putra Galuh Ciamis, 2026)
This research aims to analyze the effectiveness of the storytelling method in improving the listening and speaking abilities of grade 1 students at SDN 1 Patakaharja. At an early age, language skills, especially listening and speaking, are a very important basis for children's cognitive, social and emotional development. It is believed that the storytelling method can help students develop these two skills in a fun and interactive way. This research used a quantitative approach with a pre-experimental design and involved 30 grade 1 students as samples. Data was collected through Pretestt and posttest, observation, and interviews. The research results showed that there was a significant increase in students' listening and speaking abilities after implementing the storytelling method. The average speaking ability score increased from 57.8 to 77.0. This proves that the storytelling method is effective in improving students' language skills speaking. This research suggests that teachers and schools should more often apply storytelling methods in learning to improve students' language skills, and encourages further research to explore the long-term impact and influence on other aspects of skills.